(untitled) (Journal of the College of Basic Education, 2022)
The study aims to know the effect of using the CLM model on the achievement of second-graders middle school students and their mathematical thinking in mathematics, Where the sample consisted of (66) students, distributed to two groups, the experimental group that studied according to the CLM model, and it consists of (33) students and the control group that studied according to the usual method A of (33) students . The two researchers prepared two tests, one of which is my achievement in mathematics, the number of its paragraphs is (40) paragraphs, and the other is a mathematical reasoning test. The number of its items was (30) paragraphs, Then, the results of the experimental group’s superiority over the control group were obtained in both tests.